Minding the Children During School Holidays - Qu, L (My University, 2003)
The need for non-parental child care is an obvious and central outcome of the increased workforce participation of mothers. Given that school-age children generally have considerably longer holidays than their parents, many parents may face difficulties in organising supervision for their children for large slices of time during the year. How do they handle this problem? This article uses data from the first wave of the Household, Income and Labour Dynamics in Australia (HILDA) to examine the different non-parental care arrangements received by school-aged children under 15 years when their parents are working.
Keywords: Child Care; Families and relationships; Child Care; Families and relationships